Thinking rural health in Santal community in West Bengal: An interprofessional bottom-up approach to rural health - Widmer, Daniel (J Res Nurs, 2020)
BACKGROUND: An interprofessional and cross-cultural pedagogical project in community health for students in nursing, social work, anthropology and medicine at the end of the bachelor’s degree begun in 2014. After a rural context fieldwork in several Santal villages of West Bengal (India), students had to conduct a research project, based on a community-health topic. AIMS: This paper describes how such a pedagogical project, introducing students to ethnographic research, can initiate new ways of thinking for possible future health interventions in rural communities. METHODS: An inductive approach based on ethnography was used during the fieldwork, including observations, interviews, focus groups and local documentation. RESULTS: Our observations led to the finding that actions in rural health cannot be initiated without: promoting an interprofessional/interdisciplinary perspective and a culture of complexity and reflectivity; considering local populations in transition and not in a fixed homogenous situation; understanding more than imposing; taking into account local disease classification and local pragmatic solutions; considering the dialogue between bio-medicine and therapeutic pluralism; considering local perceptions and practices; considering care itineraries/pathways; and finally being conscious of our apostolic function. CONCLUSION: Our interprofessional pedagogical project promotes a bottom-up approach in dialogue with a global health vision.